Socioeconomic Determinants of Disability and Mortality Due to Congenital Anomalies: A Secondary Analysis of Existing Data - Behzad Karami Matin; Moslem Soofi; Ali Kazemi Karyani; Shahin Soltani; Bita Shokri; Shiva Amani; Zahra Shahbazi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Congenital anomalies are functional or structural anomalies that can occur as a single or a group of anomalies. Studies have shown that socioeconomic factors can affect congenital anomalies such that the middle- and low-income countries suffer more from the congenital anomalies. This study aimed to determine the essential socioeconomic determinants of the disability-adjusted life year (DALY) for congenital anomalies in children aged <5 years. Materials & Methods: This is a cross-sectional study using the latest available data in 2017, which were extracted from the international databases of the World Bank, the Institute for Health Metrics and Evaluation, and the United Nations Educational, Scientific, and Cultural Organization. In the study, we analyzed data from 196 countries divided into 6 geographical regions of African Region (AFRO), European Region (EURO), Pan American Health Organization (PAHO), Eastern Mediterranean Region (EMRO), Western Pacific Region (WPRO), and South-East Asia Region (SEARO). To identify the main determinants of the DALY, gross domestic products (GDP) per capita, poverty rate, government, private and external health expenditures per capita, mean years of schooling, and literacy rate were used. Data analysis was performed in STATA v.15 using the one-way ANOVA and the linear regression analysis. Results: The lowest and highest rates of DALY was reported in Luxembourg (856.29 per 100000 population) and Sudan (21714.7 per 100000 population), respectively. The AFRO and EURO regions had the highest (9392.78±4250.56), and the lowest (2969.11±1961.64) mean of DALY. In Iran, the DALY rate was reported 7721.48 per 100000 population, which was higher than those in the EURO and PAHO regions and lower than those in the AFRO and EMRO regions. The results of linear regression analysis showed that mean years of schooling was the strongest predictor of DALY (β=-0.44, P=0.001) followed by the poverty rate (β=0.36, P=0.002). The results of one-way ANOVA indicated that the rate of DALY was significantly different between different social and economic groups, and it was higher in the lower socioeconomic groups. Conclusion: Mean years of schooling and poverty rate are the strongest predictors of DALY for congenital anomalies in children under 5 years of age. Low-income countries, especially those in the AFRO and EMRO regions, are the most prone to the disability and premature death caused by congenital anomalies in children under 5 years of age compared to the high-income countries. Therefore, the equitable distribution of screening and health care services and educational infrastructures for deprived and lower socioeconomic countries should be taken into account by national and international health organizations.